Color stability and lipid oxidation in pork sausage as affected by rosemary extract and phospholipase A2: A possible role for depletion of neutral lipid hydroperoxides. Issue 4 (7th October 2021) - Whalin, James G.; Liu, Ling; Rankin, Scott A.; Zhang, Wenjing; Richards, Mark P.
Abstract: Rosemary extract (R) was added to pork sausage and compared with a novel antioxidant mixture of R and phospholipase A2 (R + P) as well as a treatment of synthetic antioxidants (Syn). Through 245 days of −20°C storage, lipid hydroperoxides (LOOH), redness, and hexanal were similar between R and R + P. However, earlier in storage, R + P decreased LOOH compared with R ( p  < .05); the neutral lipid hydroperoxides were decreased 3.3‐fold ( p  < .001), whereas free fatty acid hydroperoxides and polar lipid hydroperoxides were not significantly lowered. Through the long‐term storage, Syn had lower LOOH and hexanal than R + P yet redness was lower in Syn ( p  < .05). In unseasoned sausage, R + P demonstrated higher redness and lower hexanal values than R treatment ( p  < .05). These results suggest that R + P could offer an effective natural antioxidant in pork sausage and the antioxidant mechanism may be related to the suppression of neutral lipid hydroperoxides. Novelty impact statement: This research demonstrates a novel antioxidant mixture consisting of low concentrations of rosemary extract and phospholipase A2 (PLA2 ) in pork sausage. The fractionation of total lipids into lipid classes suggested that the antioxidant action of the mixture was related to decreasing neutral lipid hydroperoxides. The antioxidant mixture stabilized color more effectively than synthetic antioxidants in seasoned sausage yet markers of lipid oxidation were lower in the synthetic treatment.